اقتراح منهجية لتقييم التثليث الصوري وخوارزميات الربط الكثيف في نظم التوثيق ثلاثي الأبعاد القائم على الصور - الخليل, عمر (Latakia University Journal -Engineering Sciences Series, 2019)
The application of automated photogrammetry in 3D documentation of cultural heritage has increased in recent years, thanks to the development of optical sensors and improved computational capabilities. The processing chain begins by automatic search for common points between images by applying matching algorithms. The calculation of the exterior orientation parameters of images, is then achieved by photo-triangulation bundle-adjustment based. Finally, image-matching algorithms are applied to generate 3D dense point cloud, which is a key input in generating 3D models of objects. In this paper, a methodology to asses geometric accuracy of photo-triangulation of image blocks, was discussed. This methodology was applied to the output of some of the most famous automated photogrammetry software. The results shown that the true values ​​of photo-triangulation accuracy range from 3 to 5 times the theoretical accuracy. It is also possible to achieve a true resolution for the dense cloud close to the theoretical resolution, if appropriate correlation coefficients are adopted. ازداد تطبيق المساحة التصويرية المؤتمتة في التوثيق ثلاثي الأبعاد للتراث الثقافي خلال الفترة الأخيرة وذلك بفضل تطور المستشعرات البصرية وتحسّن القدرات الحسابية. تبدء سلسلة المعالجة بالبحث عن النقاط المشتركة بين الصور بشكل مؤتمت بتطبيق خوارزميات الربط. ثم ينجز حساب معاملات التوجيه الخارجي للصور بتطبيق التثليث الصوري بالتعديل بالحزم. وأخيراً تطبق خوارزميات ربط الصور وذلك لتوليد غمامة النقاط الكثيفة والتي تعتبر مدخلاً أساسياً في توليد النماذج ثلاثية الأبعاد للعناصر. تم في هذا البحث مناقشة منهجية لتقييم الدقة الهندسية للتثليث الصوري لبلوكات الصور، كما تم عرض أهم خوارزميات الربط الكثيف للصور واقتراح آلية لتقييم دقة تمييز غمامة النقاط ثلاثية الأبعاد المحسوبة من هذه الصور. تم تطبيق هذه المنهجية على مخرجات مجموعة من أشهر برامج المساحة التصويرية الآلية. أثبتت النتائج أن القيم الحقيقية لدقة التثليث تتراوح من 3 إلى 5 أضعاف الدقة النظرية. كما أنه من الممكن بلوغ دقة تمييز حقيقية لغمامة النقاط الكثيفة من فئة دقة التمييز النظرية الخاصة بها وذلك في حال اعتماد معاملات الربط المناسبة.